Effects of incentives on consumer review rating in e-commerce - Akhmetova, Anna (My University, 2018)
Scholars and companies alike have long recognized the importance of ratings and reviews in influencing customers’ purchase decisions. In an attempt to gain some degree of control over opinions posted online for their products and services companies look for new ways to generate reviews. One of the ways of achieving this is through product sampling – giving away free or discounted products in exchange for an honest opinion of the product or service. Previous research suggests that product rating is typically asymmetrically distributed forming a J-shape with extremely positive rating dominating over extremely negative rating and a low volume of mid-rated rating. This behavior is linked to the presence of the under-reporting bias and the purchasing bias. This study looks at the effects of incentives on product rating based on an example of a consumer electronics manufacturer to determine whether incentivizing reviews (in the form of a free product sample) results in a smaller variance of star ratings and, therefore, mitigates the under-reporting and the purchasing biases. The assumption taken is that even if consumers hold a negative or an indifferent opinion of a product from the start, they would be more likely to provide a review if offered an external incentive. The results of this research show, however, that product sampling results in the same degree of variance of star rating among consumers compared to the variance of rating of organically submitted reviews. In addition, this study established that extremely positive rating dominates over extremely negative rating across samples, but did not observe significant differences in means between organic and incentivized review rating.
Keywords: Ratings and reviews, product rating distribution, rating variance, purchasing bias, under-reporting bias, social exchange theory